Genealogía de la noble mentira - Miguel Catalán (Amnis)
The notion of «noble lie» has a long history. It can be found from Plato’s Republic to Leo Strauss’opus, a contemporary thinker whose thought inspires the philosophical background of the North-American neo-conservatives, who control the present Republican administration. This article goes through and analyses the main modern schools and authors who have justified political lie, i.e. a specific lie by which the political authority deceives its own people.